(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2024)
This work included the synthesis of new heterocyclic compounds containing creatinine moiety (A4-A9). These compounds were synthesized from reaction of Schiff bases (A2, A3) with glycine, thioglycolic acid, and glycolic acid to produce imidazolidine-4-one (A4, A5), thiazolidine-4-one A6, A7, and oxazolidine-4-one (A8, A9) respectively. FTIR and 1HNMR were used to identify these compounds. In vitro experiments, the antimicrobial properties of compounds (A1, A2, and A4) were evaluated and showed good results.